Shackled lily eaudiobook - Gray, Tammy L. (Winsor, 2019)
She vowed never to love . . . One would hardly see a three-story mansion, unlimited bank account, and high-end clothes as a prison. But to Kaitlyn "Issy" Summers, her family's opulence only represents pain, betrayal, and fear. To deal with her heartbreaking past, Issy finds multiple ways to self-destruct and harden her heart from ever being hurt again. He vowed to make her his . . . Grant Forester won't give up on the woman he has loved for years. He sees past the anger and bitterness to the wounded girl in need of healing. He has the secret to freedom if she would only trust him. But when darkness and deceit surfaces, their ability to choose may become nothing more than an illusion.